2009
DOI: 10.1590/s0103-64402009000500001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between periodontitis and rheumatoid arthritis and the effect of non-surgical periodontal treatment

Abstract: This study analyzed the association of periodontal disease (PD) and rheumatoid arthritis (RA). seventy-five 35-60-year-old patients were assigned to 5 groups according to the presence (+) or not (-) of PD and RA and the treatment received (TR+) or not (TR-) for PD. Group 3 uses total prosthesis (TP). Clinical and laboratory evaluations were performed at baseline, 3 and 6 months of follow-up by probing pocket depth, bleeding on probing and plaque index for PD, hAQ, DAs28, sF-36 and laboratory: AAG, esR, CRP for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(120 citation statements)
references
References 15 publications
8
100
0
12
Order By: Relevance
“…Since more severe RA is also accompanied by higher CRP levels 48,49 , higher CRP levels may be a reflection of active RA, which may contribute to an increased inflammatory state in periodontitis. Interestingly, CRP level reduces in RA patients after periodontal therapy 20 , lending support to the hypothesis that periodontitis may contribute to an increased systemic inflammation in RA.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Since more severe RA is also accompanied by higher CRP levels 48,49 , higher CRP levels may be a reflection of active RA, which may contribute to an increased inflammatory state in periodontitis. Interestingly, CRP level reduces in RA patients after periodontal therapy 20 , lending support to the hypothesis that periodontitis may contribute to an increased systemic inflammation in RA.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, a few pilot-intervention studies have pointed towards periodontitis as a risk factor for RA [17][18][19][20] . After treating periodontitis, a reduction in RA disease activity was shown, possibly related to a reduction in periodontitis associated inflammatory burden.…”
mentioning
confidence: 99%
“…Conversely, in another study, it was reported that, in patients with RA and periodontitis, although non-surgical periodontal therapy resulted in reduction of ESR, CRP, and -1 acid glycoprotein, the reductions were not statistically significant. However, in another group in the same study comprising of periodontitis patients who did not have RA, non-surgical periodontal therapy resulted in improvement of periodontal parameters with associated significant improvements in ESR, CRP, and -1 acid glycoprotein levels suggesting that RA is a multifactorial disease (Pinho Mde et al, 2009). …”
Section: Rheumatoid Arthritis and Periodontitismentioning
confidence: 99%
“…Este resultado promissor também pôde ser encontrado no estudo de PINHO et al, 2009 39 , que utilizou parâmetros clínicos, como profundidade de sondagem, placa microbiana e sangramento à sondagem para avaliação da atividade da PC, e os parâmetros DAS28 e Medical Outcomes Study 36 -Item Short -Form Health Survey (SF36) para avaliação da atividade da AR. A saber, o SF36 é um questionário com 36 itens que avalia a qualidade de vida de acordo com capacidade funcional, aspectos físicos, dor, estado geral da saúde, vitalidade, aspectos sociais, aspectos emocionais e saúde mental 37 .…”
Section: Perda óSsea Inflamatória Na Artrite Reumatoide E Na Periodonunclassified